The PD-1/PD-L pathway in rheumatic diseases - Zhang, Shuo; Wang, Li; Li, Mengtao; Zhang, Fengchun; Zeng, Xiaofeng (Journal of the Formosan Medical Association, 2021)
Autoimmune diseases are diseases in which the body produces an abnormal immune response to self-antigens and damages its own tissues. Programmed death-1 (PD-1) and its ligands (PD-Ls) have been discovered to be important negative regulators of the immune system, playing crucial roles in autoimmunity. We analyzed the existing scientific literature dealing with this issue. In this review, the PD-1/PD-L pathway in the genetic susceptibility to and pathogenesis of rheumatic diseases is discussed. The PD-1/PD-L pathway might be helpful for diagnosing, evaluating the disease activity of and treating rheumatic diseases. PD-1/PD-L gene polymorphisms are associated with a genetic predisposition to rheumatic disorders, which can provide reference information for diagnosis and disease activity. The conclusion of the crucial role of the PD-1/PD-L pathway in the pathogenesis of rheumatic diseases is consistent, but the details remain controversial. In some animal models, manipulating the PD-1/PD-L pathway could decrease disease severity. PD-1/PD-Ls may enable us to develop new therapeutics for patients with rheumatic diseases in the future. The PD-1/PD-L pathway plays crucial roles in rheumatic disease. More work is needed to provide a better mechanistic understanding of the PD-1/PD-L pathway and to facilitate the precise therapeutic manipulation of this pathway.